Pengembangan Kegiatan Kokurikuler dan Ekstrakurikuler - Khusna Shilviana; Tasman Hamami (LP2M STIT Palapa Nusantara, 2020)
Development of cocurricular and extracurricular activities is important to do, because intracuricular activities are felt to be lacking in developing students' potential. Thus, the need for companion activities that can help maximize the potential of students. The purpose of this study was to investigate the development of cocuricular and extracurricular activities. This research uses library research method (library research). The results of the research on the development of cocurricular activities, namely in their activities, must lead to activities that support intracuricular activities and student learning interests, do not contain excessive burdensome burdens, and require administration, guidance or assistance, monitoring, and assessment. While the development of extracurricular activities through several stages including: 1) needs analysis which also aims to identify the needs, potential, and interests of students. 2) determine the type of extracurricular activities through tests, questionnaires, and interviews. 3) compile an extracurricular activity program. 4) implementation phase. 5) monitoring and evaluation phase. In the development of extracurricular activities, it is also supported by education unit policies, the availability of coaches, and the availability of educational unit facilities and infrastructure